Surah Al-Fatihah as an Ethical Operating System: A Sequential Model of Qur'anic Governance, Leadership, and Community Development - Ali, Muhammad Aamir; Aamir, Nazish; Aamir, Muhammad Faseeh (Universitas Muhammadiyah Surakarta, 2026)
This study empirically examines the structural coherence of the Qur'an by analysing whether Surah Al-Fatihah functions not merely as an opening supplication but as a conceptual blueprint that unfolds progressively across subsequent surahs. Using a verse-level content analysis, eight foundational constructs derived from Surah Al-Fatihah were mapped onto four consecutive surahs-Al-Ahqaf (46), Muhammad (47), Al-Fath (48), and Al-hujurat (49)-and visualized through comparative radar charts. The findings reveal a clear sequential reallocation of thematic emphasis rather than simple repetition. Surah Al-Ahqaf prioritizes warning through historical exemplification, Surah Muhammad emphasizes moral testing and behavioural differentiation, Surah Al-Fath re-centres affirmation, praise, and prophetic legitimacy, and Surah Al-hujurat culminates in ethical regulation and communal maturity. Across this progression, core theological constructs remain constant but shift in dominance according to contextual needs, demonstrating functional rather than rhetorical coherence. The study further proposes a Qur'anic Sequential Model for sustainable community and organizational development, illustrating how moral clarity, accountability, validation, and ethical consolidation must unfold in deliberate stages. Methodologically, this research advances Qur'anic studies by integrating frequency-based coding with structural emphasis profiling, offering a replicable framework for analysing how ethical urgency and guidance evolve across the Qur'anic discourse while preserving theological unity.